2022
DOI: 10.1136/jitc-2021-004206
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell transcriptomics reveals a low CD8+T cell infiltrating state mediated by fibroblasts in recurrent renal cell carcinoma

Abstract: PurposeRecurrent renal cell carcinoma(reRCC) is associated with poor prognosis and the underlying mechanism is not yet clear. A comprehensive understanding of tumor microenvironment (TME) of reRCC may aid in designing effective anticancer therapies, including immunotherapies. Single-cell transcriptomics holds great promise for investigating the TME, however, this technique has not been used in reRCC. Here, we aimed to explore the difference in the TME and gene expression pattern between primary RCC (pRCC) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 56 publications
1
22
0
Order By: Relevance
“…The recruitment of CAF within the ccRCC microenvironment is proposed to occur via interactions with malignant PTEC that upregulate COL20A1, COL28A1, and TGFB1 (29). These infiltrating CAF are able to reduce CD8 + T cell infiltration within ccRCC microenvironments, particularly within recurrent ccRCC as identified by a recent single-cell transcriptomics study (Figure 3) (73). In this study, the immunosuppressive behavior mediated by CAF was attributed to the secretion of Galectin-1 (Gal1), which was noted within the captured transcriptome by the substantial expression of LGALS1.…”
Section: Cancer-associated Fibroblasts In Recurrent and Locally Invas...mentioning
confidence: 56%
“…The recruitment of CAF within the ccRCC microenvironment is proposed to occur via interactions with malignant PTEC that upregulate COL20A1, COL28A1, and TGFB1 (29). These infiltrating CAF are able to reduce CD8 + T cell infiltration within ccRCC microenvironments, particularly within recurrent ccRCC as identified by a recent single-cell transcriptomics study (Figure 3) (73). In this study, the immunosuppressive behavior mediated by CAF was attributed to the secretion of Galectin-1 (Gal1), which was noted within the captured transcriptome by the substantial expression of LGALS1.…”
Section: Cancer-associated Fibroblasts In Recurrent and Locally Invas...mentioning
confidence: 56%
“…GSEA analysis showed that high-risk group genes were mainly enriched in immune-related biological processes, such as activation of the immune response, adaptive immune response based on somatic ecombination of immune receptors built from immunoglobulin superfamily domains, antigen receptor mediated signalling pathway, B cell activation, B cell-mediated immunity ( Figure 8A ), the low-risk group genes were mainly enriched in fatty acid metabolic process, spliceosomal snrnp assembly, spliceosomal tri snrnp complex assembly, apical part of cell, anion transmembrane transporter activity ( Figure 8B ). Immunotherapy is now a treatment strategy with great potential after targeted therapy for patients with KIRC, and the tumor immune microenvironment is an important factor influencing the response to immunotherapy ( 20 , 21 ). We used the MCP-counter algorithm to estimate immune cell scores for each patient with KIRC and then calculated their correlation with risk scores by Pearson’s method.…”
Section: Resultsmentioning
confidence: 99%
“…It suggested that the increased CENPA expression was inversely related to the abundance levels of B cells and CD8 + T cells in PRCC. Besides, it has been shown that the low levels of B cells and CD8 + T cells in tumor tissues are associated with the prognosis of cancer patients [ 19 21 ], containing the poor prognosis of PRCC. Several other studies report that the high levels of tumor-infiltrating Tregs in BC, HCC, lung cancer, gastric cancer, and ovarian cancer were significantly associated with the poorer prognosis [ 22 26 ].Therefore, we reasoned that CENPA might affect patient prognosis by modulating the immune infiltration in PRCC.…”
Section: Discussionmentioning
confidence: 99%